MEKANISME PERAWATAN KITCHEN EQUIPMENT PADA KITCHEN SECTION DI FOX HOTEL PEKANBARU - Agustiani "; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The kitchen equipment maintenance mechanism consist of several items: 1) Electric Frayer, 2)Broiler, 3) Salamander, 4) Soup Kettle, 5) Steam Cooker, 6) Steam Table, 7) Gas Table, 8) Barbeque Table, 9) Noodle Range. This study aims: to determine the mechanism for maintaining kitchen equipment in the kitchen section at Fox Hotel Pekanbaru. This study used a qualitative descriptive method with research subjects consisting of stewards and executive chefs. Data collection was carried out by means of observation, interviews, and documentation. Data analysis in this study was data reduction, data presentation and conclusion drawing. And the results of study indicate that the mechanism for maintaining kitchen equipment in the kitchen section of Fox Hotel Pekanbaru uses several chemicals from iclean products, including: Forcemaxx which is used to clean oily, slippery and fatty dirt on the kichen floor,Q-San for the sanitation process on the surface. or equipment, Rinsemaxx a concentrated material that functions to speed up the drying process in the dishwasher and glass washer, generalcleaner plus a versatile cleaning product for all surfaces such as from food scraps, metal poliz: a cleaner to remove stubborn stains on metal surfaces such a stainless steel, iron and others. Stainaway Soaking Powder is specially formulated to remove stubborn stains from coffe, tea and kitchen spices. Keywords: Kitchen Equipment Maintetance Mechanism